ANALISIS HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI DESA HEGARMANAH, DESA MALEBER, DAN DESA SABANDAR, KECAMATAN KARANG TENGAH, CIANJUR,JAWA BARAT - Asiah, Nur (Prosiding Seminar Nasional Berseri, 2017)
Nutrition of infants and toddlers in order to ensure growth is one of the fundamental effort to ensure the attainment of the highest quality of the next generation. Feeding is best since birth that is exclusive breastfeeding, breastfeeding until age 6 months and continued breastfeeding up to 2 years is his best efforts. From various research Breast milk is the best food for babies,but it is often overlooked by mothers. This study aimed to determine characteristics and Knowledge Capital Relationship with ASI Granting Exclusive Desa Hegarmanah, Maleber,and Sabandar, Karang Tengah subdistrict, Cianjur, West Java. The population was mothers with infants aged 6 months-1 year. This study used cross sectional design. Collecting data using questionnaires with respondents as many as 235 people. The data were analyzed using univariate and bivariate. To see a statistically significant relationship chi square test with an alpha <0.05. Results obtained exclusive breastfeeding mothers more than mothers who did not breastfeed exclusively in a row from the village Maleber,Hegarmanah and Sabandar village,namely 92%, 69%, and 88. Mothers aged 20-35 more than mothers aged <20 and> 35 years in a row is equal to 74%, 73% and 78%. Mothers who do not work more than mothers who worked as follows: 90%, 87% and 91%. Mothers with low education (not completed primary school, graduated from elementary school and junior high school graduation more than mothers who had high school and PT, respectively in the amount of 84%, 75% and 71%. Mothers who are knowledgeable about breastfeeding low, more many of the mothers who have knowledge of high levels, respectively, namely 60.4%, 69% and 60%.